1995
DOI: 10.1295/polymj.27.136
|View full text |Cite
|
Sign up to set email alerts
|

Photochromism of 2-Chloro-N-salicylideneaniline in Amorphous Polymer Solids

Abstract: ABSTRACT:Photochromism of 2-chloro-N-salicylideneaniline, Sa(H,2-Cl), molecularly dispersed in amorphous polymer matrices was investigated under conventional steady-state irradiation. The final conversion of photochromic reaction in amorphous polymers was found to decrease with temperature due to notable influence on a thermal back reaction. The effect of polymer matrix on the thermal decay reaction was explained by the half-life (l/t, 12 ) of the colored species and concept of free volume of polymer matrices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…To investigate the contribution of random packing on the phosphorescence of trimeric copper(I) pyrazolates, the three complexes were monodispersed in PMMA films (concentration 1.0 × 10 −3 mol kg −1 ). The free volume of PMMA was small enough to partially hinder the phenyl rotation, and the higher excitation energy of the polymer compared to that of the trimers decreased greatly the possibility of ET and EM processes; thus, the polymer was suitable to simulate this pure hindrance effect . The luminescence spectra of the complexes are shown in Figure S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the contribution of random packing on the phosphorescence of trimeric copper(I) pyrazolates, the three complexes were monodispersed in PMMA films (concentration 1.0 × 10 −3 mol kg −1 ). The free volume of PMMA was small enough to partially hinder the phenyl rotation, and the higher excitation energy of the polymer compared to that of the trimers decreased greatly the possibility of ET and EM processes; thus, the polymer was suitable to simulate this pure hindrance effect . The luminescence spectra of the complexes are shown in Figure S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Another approach that has been investigated is the incorporation of small molecule anil compounds into an amorphous polymer matrix. 20,21 In this case, a photochromic response is observed upon steady state irradiation of polymer films with UV light. The phenomenon is again closely related to the free volume in the polymer film and the freedom of molecular motion of the anil molecule in the amorphous matrix.…”
Section: Introductionmentioning
confidence: 99%
“…63−65 Yin et al studied the photochromism and photophysical properties of SA derivatives in several polymer matrices. 63 Nomura et al reported multicolor fluorescence of a π-conjugated oligomer containing SA in the main chain. The emission originated from the radiation process from the proton-transferred tautomer to its metastable ground state.…”
Section: ■ Introductionmentioning
confidence: 99%